ACADEMIC PARAPHRASE: CORNELL NOTE TAKING SEBUAH CARA MENGHINDARI PLAGIARISME DALAM MENULIS KARYA ILMIAH BERBAHASA INGGRIS DI KALANGAN MAHASISWA - Yuniarti Yuni (Pedagogik : Jurnal Ilmiah Pendidikan dan Pembelajaran Fakultas Tarbiyah Universitas Muhammadiyah Aceh, 2015)
Plagiarism of writing thesis is often happened in academicians level especially by students.  The level of plagiarism is called when students often quote and duplicate references using all original writer’s idea into their thesis and without putting the source of information.  To avoid the duplication of writing the original writer’s idea,  there is a way which can be applied that is by paraphrasing sentences. In this case, all students must know how to paraphrase by their own word without missing or changging the original meaning well and inserting name of author. the Cornell note taking is one of methods that can be used by students when they would like to get an important information from the text correctly. Besides, Cornell note taking is used also to focus on recording important concepts like vocabulary, date, people, theory and process.  One of the objectives to use this note taking is for students who are really need to record the references as a theory for  supporting their findings. The skill of Cornell note taking should be practiced continously in order the students are able and get familiarize to use it.  The technique of using the Cornell note taking, first one someone should make a column format of Cornell note taking, then change difference words with the synonym one, change the structure, and change parts of speech. All paraphrase sentences written by students should not change the original meaning and still having the same length of quotation with the original one.